Rasio Komunikatif Kelompok Tani (Studi tentang Komunikasi Kelompok Tani Arum Sari dengan Perusahaan Corteva Agriscience Indonesia) - Muhar, Ardy Choisal; Suhartini, Elly (Jurnal ENTITAS SOSIOLOGI, 2021)
Agriculture is a special concern in Indonesia's development program. This program seeks to pay attention to the capacity of farmers through the existence of agricultural supporting institutions, namely farmer groups. Farmer group forums are used as a means of aspiration and communication between farmers in the sustainability of the agricultural sector. This is done by the Arum Sari Farmers Group located in Krajan II Hamlet, Kembiritan Village. However, there are limitations of production factors (land, work, capital) which pose a threat so that farmer groups look for alternative ways by establishing partnerships with companies. This study aims to analyze the partnership run by the Arum Sari Farmer Group with the Corteva Agriscience Indonesia company. Then it will be analyzed using the theory of Jurgen Habermas regarding the communicative ratio. The type of research used in this study is a qualitative method with a phenomenological approach. In determining the informants using purposive sampling technique and using 3 data collection techniques, namely observation, in- depth interviews, and documentation. In testing the validity of the data, using source triangulation, until the analysis technique uses data condensation, data presentation, and drawing conclusions. The results of this study are the communicative ratio plays an important role in the use of communication language to reach a consensus word to establish a partnership. This partnership is also in the form of a subcontracting scheme that requirespartner groups to produce components needed by partner companies as part of their production.Keywords: communicative ratio, partnership and farmer group Pertanian menjadi perhatian khusus dalam program pembangunan negara Indonesia. Program ini berupaya memperhatikan kapasitas petani melalui adanya kelembagaan penunjang pertanian, yakni kelompok tani. Forum kelompok tani dijadikan sebagai sarana aspirasi dan komunikasi antar petani dalam keberlangsungan sektor pertanian. Hal ini dilakukan oleh Kelompok Tani Arum Sari yang berada di Dusun Krajan II, Desa Kembiritan. Namun, muncul keterbatasan faktor produksi (lahan, kerja, modal) yang menjadi ancaman sehingga kelompok tani mencari jalan alternatif dengan menjalin kemitraan bersama perusahaan. Penelitian ini bertujuan untuk, menganalisis mengenai kemitraan yang dijalankan oleh Kelompok Tani Arum Sari dengan perusahaan Corteva Agriscience Indonesia. Kemudian akan di analisis menggunakan teori dari Jurgen Habermas mengenai rasio komunikatif. Jenis penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan fenomenologis. Dalam penentuan informan menggunakan teknik Purposive Sampling serta menggunakan 3 teknik pengumpulan data yaitu observasi, wawancara mendalam, dan dokumentasi. Dalam pengujian keabsahan data, menggunakan triangulasi sumber, Hingga untuk teknik analisis menggunakan kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah rasio komunikatif berperan penting dalam penggunaan bahasa komunikasi hingga mencapai kata konsensus untuk menjalin kemitraan. Kemitraan yang dijalankan ini juga berbentuk pola subkontrak yang mengharuskan kelompok mitra memproduksi komponen yang diperlukan perusahaan mitra sebagai bagian dari produksinya.Kata kunci: rasio komunikatif, kemitraan, dan kelompok tani.